Pengaruh Metode Kooperatif Learning Tipe Snowball Throwing Terhadap Kemampuan Komunikasi Matematika Siswa SMP Negeri 5 Padangsidimpuan - Wulan Eka Putri Siregar; Susi Sulastri Lubis; Nova Christina Dewi (Jurnal Cermatika, 2024)
This study aims to see whether or not there is an effect of snowball throwing type cooperative learning method on mathematical communication skills of seventh grade students of SMP Negeri 5 Padangsidimpuan. This type of research is a pseudo experiment. The research samples were VII-5 and VII-8 classes totaling 40 students. The data collection technique used is an essay-shaped test of 5 questions that have been tested with pretest and posttest reliability using the Cronbach's alpha formula in the spss application with a significant level of 5% and n = 20 which is then compared to the r table obtained a value of 0.444. It turns out that rcount> rtabel is (0.608>0.444) for the pretest and (0.556>0.444) for the posttest. Data analysis using normality test, homogeneity test and hypothesis testing. The pretest results of the average value of the experimental and control classes were 63.8 and 64.05, respectively. For the posttest results, the average value of the experimental class was 82.75 and the control class was 75.65. The normality test of the pretest and posttest of the experimental and control classes has sig>0.05 and the homogeneity test of the significant value is above 0.05 or sig>0.05, so the experimental class and control class have homogeneous data conditions. For the hypothesis test, a significant value of 0.039 or 0.039 <0.05 was obtained. Thus the researcher concluded that there was an effect of the snowball throwing type cooperative learning method on the mathematical communication skills of SMP Negeri 5 Padangsidimpuan.